2008
DOI: 10.1115/1.2818775
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Turbulent Convective Heat Transfer and Pressure Loss of Alumina/Water and Zirconia/Water Nanoparticle Colloids (Nanofluids) in Horizontal Tubes

Abstract: The turbulent convective heat transfer behavior of alumina (Al2O3) and zirconia (ZrO2) nanoparticle dispersions in water is investigated experimentally in a flow loop with a horizontal tube test section at various flow rates (9000<Re<63,000), temperatures (21–76°C), heat fluxes (up to ∼190kW∕m2), and particle concentrations (0.9–3.6vol% and 0.2–0.9vol% for Al2O3 and ZrO2, respectively). The experimental data are compared to predictions made using the traditional single-phase convective heat transfer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
3
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(190 citation statements)
references
References 17 publications
8
153
3
4
Order By: Relevance
“…The results show that, at constant velocity, the heat transfer coefficient of the 0.33 vol% MWCNT-water nanofluid is 3.3% lower, at 0.75 vol%, it is 6.6% lower and at 1.0 vol%, it is 12.6% lower than that of distilled water. This trend of lower heat transfer coefficients in nanofluids compared with water was also experienced by Pak and Cho [6], Williams et al [41] and Yu et al [40]. However, at very high velocities, the heat transfer coefficients of the 0.33 vol% MWCNT-water nanofluid equal that of the distilled water.…”
Section: Convective Heat Transfer Of Mwcnt-water Nanofluidsmentioning
confidence: 70%
See 1 more Smart Citation
“…The results show that, at constant velocity, the heat transfer coefficient of the 0.33 vol% MWCNT-water nanofluid is 3.3% lower, at 0.75 vol%, it is 6.6% lower and at 1.0 vol%, it is 12.6% lower than that of distilled water. This trend of lower heat transfer coefficients in nanofluids compared with water was also experienced by Pak and Cho [6], Williams et al [41] and Yu et al [40]. However, at very high velocities, the heat transfer coefficients of the 0.33 vol% MWCNT-water nanofluid equal that of the distilled water.…”
Section: Convective Heat Transfer Of Mwcnt-water Nanofluidsmentioning
confidence: 70%
“…[40], Williams et al [41] and Liu and Liao [16]. The properties of the nanofluids, such as the thermal conductivity and viscosity were determined from Equation 2 and 3.…”
Section: Comparison Of Results With Existing Heat Transfer Correlationsmentioning
confidence: 99%
“…For validation the present model predictions are compared with the experimental data of Williams et al [43] in Figure 2. Comparisons are done for three concentrations of 0.2%, 0.5% and 0.9% for ZrO2-water nanofluids.…”
Section: Validationmentioning
confidence: 99%
“…Some researchers [13][14][15] reported that heat transfer in nanofluids can be modelled using classical correlations (based on Maxwell) for single-phase fluids with adjustment for properties with the nano-particles. Others stated that the heat transfer behaviour obeys a two phase model with variation due to concentration of nano-particles varying in the flow.…”
Section: -Introductionmentioning
confidence: 99%